Code Switching in Communication in Donggala Community - Jamiluddin Jamiluddin; Ulinsa Ulinsa; Widya nasfa (PT Publikasiku Academic Solution, 2023)
The focus of the problems for this research are: (1) Determining the form of code-switching in communication in the community of Gunung Bale Village, Donggala, (2) The factors causing code-switching in communication among the community of Gunung Bale Village, Donggala. The aims of this study are (1) to describe the form of code-switching in communication among the community of Gunung Bale Village, Donggala, (2) to describe the factors that cause code-switching in communication in the community of Gunung Bale Village, Donggala. This study uses a qualitative method. The process of obtaining data and data sources Is through oral data in the community of Gunung Bale Village, Donggala. Data collection techniques used are recording technique, observing technique, and note-taking techniques Data analysis techniques through the process of (1) data collection, (2) data reduction, and (3) data verification. The results showed that the forms of code-switching from the results of this study are the internal form of code-switching in the form of code-switching from Bugis to Indonesian, the external code-switching in the form of (1) code-switching from Indonesian to Kaili, Undepu dialect, (2) code-switching from Kaili, Undepu dialect to Indonesian. The factors that caused code-switching to Kaili, Undepu dialect in the Gunung Bale Village community, Donegal, are (1) speaker factors, (2) speech partner factors, (3) third-person presence factors, and (4) topic change factors.